2018
DOI: 10.1007/s10551-018-3989-9
|View full text |Cite
|
Sign up to set email alerts
|

Denial of Corruption: Voluntary Disclosure of Bribery Information

Abstract: This study explores the rationality behind firms' decision to admit or deny their involvement in bribery when responding to confidential surveys conducted by international agencies (such as the World Bank). Specifically, we posit that firms' reluc-tance to provide accurate information about their engagement in bribery is at least to some extent contingent on certain situ-ational factors. In other words, we claim that this behavior is context dependent. The paper uses the notions provided by the theory of plann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 32 publications
0
4
0
1
Order By: Relevance
“…To address these limitations, business ethics scholars have become more focused upon enhancing our understanding of the various types of corruption that firms encounter in foreign markets (Luiz and Stewart 2014;Van Vu et al 2018), as well as the different strategic, structural and operational responses of MNCs to heightened levels of corruption (Godinez and Liu 2018;Orudzheva et al 2018;Xie et al 2018). In doing so, ethics scholarship (Clark and Brown 2015;Gago-Rodríguez et al 2018;Hauser 2018;Remišová et al 2018) is generating new research insights that are helping to inform the efforts of anti-corruption scholars who endeavor to design better strategies to curb MNC engagement in foreign market corruption.…”
Section: Introductionmentioning
confidence: 99%
“…To address these limitations, business ethics scholars have become more focused upon enhancing our understanding of the various types of corruption that firms encounter in foreign markets (Luiz and Stewart 2014;Van Vu et al 2018), as well as the different strategic, structural and operational responses of MNCs to heightened levels of corruption (Godinez and Liu 2018;Orudzheva et al 2018;Xie et al 2018). In doing so, ethics scholarship (Clark and Brown 2015;Gago-Rodríguez et al 2018;Hauser 2018;Remišová et al 2018) is generating new research insights that are helping to inform the efforts of anti-corruption scholars who endeavor to design better strategies to curb MNC engagement in foreign market corruption.…”
Section: Introductionmentioning
confidence: 99%
“…Second, we argue that although scandals have the potential to cripple morale, destroy reputation, and often stifle the ability to create and capture value in the short term, they also represent opportunities for organisational renewal. In this regard, we are of the view that evading and denying scandals can be self‐defeating as organisations may risk losing the opportunity to confront and learn from the shadows of history in the form of corruption and bribery scandals (Gago‐Rodríguez et al, 2020). Rather than evading them, we encourage organisations to take the ‘path less travelled’ by developing their own Vergangenheitsbewältigung —a pioneering idea developed by the German state to help it to collectively confront its citizens' complicity in the crimes committed by the Nazi regime (Schwarz, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that in insecure and unstable environments characterized by an overall culture of illegality, corruption seems to be more faded than in environment where citizens respect the law, encourages others to respect it and rejects illegality (Pirtea et al, 2019; Nelken, 2020). Tolerance of or even acceptance of corruption in wider social environments may lead to a denial of personal responsibility and, thus, strengthen the “rationalization of corruption” (Gago‐Rodríguez et al, 2020). Several studies recognize a common initial stage: when corrupt practices produce a positive outcome, they are included into an environmental memory, to be used in the future (Arellano‐Gault, 2019).…”
Section: The Conceptual Modelmentioning
confidence: 99%